2009
DOI: 10.1037/a0016370
|View full text |Cite
|
Sign up to set email alerts
|

Eyeblink conditioning leads to fewer synapses in the rabbit cerebellar cortex.

Abstract: Eyeblink conditioning involves the pairing of a conditioned stimulus (tone) to an aversive unconditioned stimulus (air puff). Although the circuitry that underlies this form of learning is well defined, synaptic changes in these structures have not been fully investigated. This experiment examined synaptic structural plasticity in the cerebellar cortex, a structure that has been found to modulate the acquisition and timing of the conditioned response. Long-term depression of Purkinje cells (PCs) in the cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Previous in vitro studies have shown decreases in synaptic AMPAR responses in slice preparations but no structural changes after LTD induction in cultured PCs (24). Other in vivo studies demonstrated PF-PC synaptogenesis induced by learning a complex acrobatic motor skill (25) or PF-PC elimination by eyeblink conditioning (26). In the vestibular ocular reflex (VOR), which shares common output pathways with HOKR (1, 4), gaindecrease but not gain-increase adaptation was improved by estradiol treatment, which also increased PF-PC synapse density (27).…”
Section: Discussionmentioning
confidence: 97%
“…Previous in vitro studies have shown decreases in synaptic AMPAR responses in slice preparations but no structural changes after LTD induction in cultured PCs (24). Other in vivo studies demonstrated PF-PC synaptogenesis induced by learning a complex acrobatic motor skill (25) or PF-PC elimination by eyeblink conditioning (26). In the vestibular ocular reflex (VOR), which shares common output pathways with HOKR (1, 4), gaindecrease but not gain-increase adaptation was improved by estradiol treatment, which also increased PF-PC synapse density (27).…”
Section: Discussionmentioning
confidence: 97%
“…The other possibility is that the protein synthesis may be related to restructuring of cerebellar cortical neural circuitry. A decrease in the number of pf-PC synapses has been suggested in the rabbit cerebellar hemisphere after acquisition of eyeblink conditioning (Connor et al, 2009) and in the mouse flocculus after long-term HOKR adaptation (Nakadate et al, 2004). The reduced pf-PC synapses may decrease the tonic inhibitory drive of Purkinje cells on vestibular or cerebellar nuclear neurons.…”
Section: Role Of Protein Synthesis In Memory Transfermentioning
confidence: 98%
“…Changes in synapse structure have also been found in the cerebellar cortex following eyeblink conditioning. Rabbits given 3 d of eyeblink conditioning showed a reduction of excitatory parallel fiber synapses with Purkinje cells (Connor et al 2009). Thus, the morphological studies of synaptic plasticity have found synaptic changes that might underlie an LTP-like mechanism in the anterior interpositus nucleus and an LTD-like mechanism in the cerebellar cortex.…”
Section: Localization Of the Memory Trace Within The Cerebellummentioning
confidence: 99%